INDEPENDENT WORK METHODS FOR FORMING STUDENTS' COGNITIVE COMPETENCE THROUGH LITERARY AND THEORETICAL CONCEPTS IN THE SYSTEM OF DIFFERENTIAL LITERARY EDUCATION - Matkarimova Sayyora Shavkatbek kizi (Web of Journals Publishing, 2023)
The article talks about independent work methods for forming students' cognitive competence through literary-theoretical concepts in the system of differential literary education.
Keywords: literature, differential, cognitive competence, independent work, individual approach, homogeneous group.